2010
DOI: 10.1016/j.polar.2010.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for widespread endemism among Antarctic micro-organisms

Abstract: Understanding the enormous diversity of microbes, their multiple roles in the functioning of ecosystems, and their response to large-scale environmental and climatic changes, are at the forefront of the international research agenda. In Antarctica, where terrestrial and lacustrine environments are predominantly microbial realms, an active and growing community of microbial ecologists is probing this

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
82
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 141 publications
(88 citation statements)
references
References 71 publications
3
82
1
2
Order By: Relevance
“…Even though temperate habitats from alpine areas in New Zealand and marine influenced sites in Europe are not fully comparable to polar habitats, these results are corroborated by studies on eukaryote biogeography finding bi-polar distributions of fungal OTUs (Cox et al, 2016), testate amoebae (Yang et al, 2010), and bryophyte species (Biersma et al, 2017). These findings suggest that the global dispersal of certain (microbial) species is combined with environmental selection shaping bacterial communities in the polar regions (Vyverman et al, 2010;Chong et al, 2015;Cox et al, 2016), though temporal (Rochera et al, 2010) or spatial (Villaescusa et al, 2013) variability in environmental conditions can cause differences among prokaryotic meta-communities in polar habitats. Highly seasonal conditions in the polar regions (Chong et al, 2015), such as the absence of light in winter (Alonso-Saez et al, 2012) freezing and limited freshwater availability Mohit et al, 2017) and low temperatures (Yergeau et al, 2007(Yergeau et al, , 2012Kleinteich et al, 2012) may cause the observed differences between polar and non-polar communities, since non-polar regions exhibit more moderate environmental conditions.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…Even though temperate habitats from alpine areas in New Zealand and marine influenced sites in Europe are not fully comparable to polar habitats, these results are corroborated by studies on eukaryote biogeography finding bi-polar distributions of fungal OTUs (Cox et al, 2016), testate amoebae (Yang et al, 2010), and bryophyte species (Biersma et al, 2017). These findings suggest that the global dispersal of certain (microbial) species is combined with environmental selection shaping bacterial communities in the polar regions (Vyverman et al, 2010;Chong et al, 2015;Cox et al, 2016), though temporal (Rochera et al, 2010) or spatial (Villaescusa et al, 2013) variability in environmental conditions can cause differences among prokaryotic meta-communities in polar habitats. Highly seasonal conditions in the polar regions (Chong et al, 2015), such as the absence of light in winter (Alonso-Saez et al, 2012) freezing and limited freshwater availability Mohit et al, 2017) and low temperatures (Yergeau et al, 2007(Yergeau et al, , 2012Kleinteich et al, 2012) may cause the observed differences between polar and non-polar communities, since non-polar regions exhibit more moderate environmental conditions.…”
Section: Discussionmentioning
confidence: 66%
“…The percentage of these uniquely present OTUs was highest in non-polar samples in our dataset and likely reflects the higher similarity of the polar compared to non-polar regions. The somewhat larger fraction of endemic OTUs in the Antarctic compared to the Arctic may partially be explained by more extreme environmental conditions in Antarctica (Vyverman et al, 2010), but may also reflect the geographical situation of the two regions. The terrestrial Arctic has broad northsouth connections over continental land masses, ocean sectors and ecoclimatic zones, whereby wind, water currents and migrating animals may serve as vectors for species dispersal.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations